Specific Determinants of Stunting Toddlers in Lampung Province: Spatial Data Analysis - Yushananta, Prayudhy; Muslim, Azhari; Rusli, Yenni (Jurnal Kesehatan, 2023)
The prevalence of stunting still varies between districts, even though it shows a decreasing trend nationally. Variations in the correlation of specific determinants are characteristic of each region that must be considered when designing stunting control strategies, considering the significant future impacts. The study aims to identify specific determinants of stunting among toddlers between districts in Lampung Province. With an ecological design, the study uses aggregate data from the Indonesian Nutrition Status Study Report 2022 and Welfare Statistics of Lampung Province 2022. The analysis was carried out in stages with the Moran's Index and Local Moran's Index (LISA), using ArcMap and GeoDa software. Based on the analysis results, there are three districts with stunting prevalence above the national average and ten districts above the provincial average. Comparison year over year (YoY) shows that the two districts have increased from low to high or very high. We also found six variables specifically correlated with the prevalence of stunting: access to safe drinking water and sanitation, poverty, birth attendant, age at pregnancy, and length of breastfeeding. Increasing and improving specific determinants is an essential step in designing control strategies.